PEWARNAAN TOTAL ANTIAJAIB ℋ-DEKOMPOSISI SUPER PADA GRAF PRISMA DAN SUBDIVISI GRAF PRISMA SERTA KAITANNYA DENGAN KETERAMPILAN BERPIKIRTINGKAT TINGGI - Viantasari, Erwinda; Dafik, D; Fatahillah, Arif (Kadikma, 2018)
All graphs in this paper are unorientated, simple, connected, and planar graphs. Super ℋ-decomposition antimagic total labeling on a graph is a bijective function that fulfills for every two neighboring isomorphic subgraphs (just share vertex elements and minimumly share one vertex) and , , where for each , , is a subgraph of graph that contains vertexs and edges , , , . Next, it is called coloring if many of different weights is at its minimum. In this paper, we will find the existence of chromatic numbers of super ℋ-decomposition antimagic total coloring on Prism Graph and subdivision graph of Prism graph. In this research will also related with high order thinking skills with six aspects as indicators. Those aspects are Remembering, Understanding, Applying, Analysing, Evaluating, and Creating. The results of this research are four theorems about super ℋ-decomposition antimagic total coloring on Prism Graph and subdivision of Prism graph and related with high order thinking skills. Keywords: Super -Decomposition Antimagic Total Coloring, Prism Graph and Subdivision of Prism Graph, High Order Thinking Skills